The influence of inorganic nitrogen fertilizer forms on micronutrient retranslocation and accumulation in grains of winter wheat - Barunawati, Nunun (Frontiers Media S.A., 2013)
The fortification of cereal grains with metal micronutrients is a major target to combat human malnutrition of Fe and Zn. Based on recent studies showing that N fertilization can promote Fe and Zn accumulation in cereal grains, we investigated here the influence of nitrate- or ammonium-based N fertilization on the accumulation of Fe, Zn, and Cu as well as metal chelator pools in flag leaves and grains of winter wheat. Fertilization with either N form increased the concentrations of N and of the metal chelator nicotianamine (NA) in green leaves, while 2'-deoxymugineic acid (DMA) remained unaffected. Despite the differential response to N fertilization of NA and DMA levels in flag leaves, N fertilization remained without any significant effect on the net export of these metals during flag leaf senescence, which accounted for approximately one third of the total Fe, Zn, or Cu content in leaves. The significant increase in the accumulation of Fe, Zn, and Cu found in the grains of primarily ammonium-fertilized plants was unrelated to the extent of metal retranslocation from flag leaves. These results indicate that an increased N nutritional status of flag leaves promotes the accumulation of Fe, Zn, and Cu in flag leaves, which is accompanied by an increased pool of NA but not of DMA. With regard to the far higher concentrations of DMA relative to NA in leaves and leaf exudates, DMA may be more relevant for the mobilization and retranslocation of these metals in high-yielding wheat production.